Counseling the apostates in Selangor: An overview - Wan Muhammad, Ramizah (Universiti Malaya, 2016)
Islam is the religion of advice. Counseling the apostates is a form of helping them so that there is a possibility of them reverting to Islam. Apostasy is considered as one the hudud crimes in Islam and punishable with death penalty subject to certain requirements, according to Muslim jurists. In Malaysia, apostasy is considered as one of the syariah criminal offences in the Malaysian syariah courts but punishable with fine and imprisonment only in which these kinds of punishments are known as ta’zir punishments. This paper discusses the jurisdiction of syariah courts in Malaysia to hear cases on apostasy with reference particularly to the declaration that a person is no longer a Muslim or that a deceased is a Muslim or not at the time of his death for the purpose of burial and any other death rituals according to one’s religion. Some decided court cases will be shared at this juncture. The author also highlights the procedures prior to a person (or an applicant) becoming murtad (apostate) as prescribed in the Islamic law governing all Muslims in Malaysia. One of the procedures that an applicant must undergo is counseling and education session for 90 days. Hence, this paper also discusses the appropriate mode of counseling, programs, activities and so forth to use in correcting their faith and eventually to restore the applicant to the original status of being a Muslim. The purpose of this paper is to examine the current practice of counseling the applicants on this issue. To what extent is the method used effective? The research questions for this study are: what kind of effective counseling that can be used to make a person change his mind from becoming a murtad? In this respect, will counseling be enough or should it be accompanied by other effective programs/activities? What are the reasons for apostates to change their faith? In the light of these discussions, the study makes a proposal for the best and the most appropriate ways to help restore the faith of an apostate to Islam.